359 The HEEADSSS app: a service evaluation of the psychosocial screening app in young people. (17th August 2022) - lora, Paterson; James, David; Patel, Sanjay
Abstract : Aims: HEEADSSS is an acronym that stands for: Home, Education and/or employment, Eating, Activities, Drugs, Sex, Suicide, Safety. The use of a self-screening HEEADSSS app that signposts young people to local services is newly-developed and has little evaluation 1. To discover what the experience of adolescents undergoing self-administered HEEADSSS screening is 2. To understand staff attitudes and experience with HEEADSSS screening and the HEEADSSS app 3. To understand the barriers to HEEADSSS screening in the Emergency Department Methods: A service evaluation of young people aged 13-17 and staff was carried out between 11 th October and 30 th November. Adolescents, who used the app, were asked to fill out a survey. All staff in the children's emergency department were invited to fill out the survey. Results: Young people: From 100 young people 74% preferred to use the app alone, 24% preferred to use it with a parent/carer and 2% preferred a healthcare professional to be present. 98% of adolescents either agreed or strongly agreed that the app was easy to use. 96% of adolescents either agreed or strongly agreed that the app questions were appropriate. 82% found resources. 90% of those who found resources agreed or strongly agreed that the resources were helpful. Staff: We received a response from 32 of X staff. All doctors had heard of HEEADSSS screening, 45% of nurses had not. 39% of clinicians never see an adolescent get screened and 39% see <50% screened.. By profession, nurses cited a lack of training and resources to be their biggest barrier while doctors cited time. 73% of all staff have never used the HEEADSSS app. The majority of staff found the app easy to use and agreed the questions on the app were appropriate. Conclusion: HEEADSSS screening via the self screening app is popular with young people and should be offered to all those who present to hospital. Self-screening will help tackle the time and resources barriers. Its use could be expanded to outpatient clinics, primary care and education. All staff, especially nurses, require education of the HEEADSSS app and its utility.